(3QSGFds - (3GdMGQKj GdYGedj GdgePGfj, jgGA GdOjf, MeO Hf MSjf Hf YHO GdUeO, (B1031 (3g`s
(3ChdgG (B:s
... (3hYdi GdQCj GdKGfj LQi JYQja GdbhGYO HCfgG ZSd HGdeGA Ch eSM HGdJQGH eJYdb HGdHOf , ZSd GdKhH hfMhg hONd HGdUdGMjI eG NQL SGHbG Ch fbV WQOg (B...s
(3BNQgG (B:s
... (3ajfhj aj cd djdI ajbhd CHjJ Hefi gg GddjdI aj ML GdESdGe ML GdJeJY dhLhHg bQHI Edi Gddg hjQej GdLeQGJ GdKdGK aj cd jhe Jdc GdCjGe hgj CjGe GdJTQjb (B....s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\102s
(3GdCYdGe (B6\103s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis